Prediksi Pajak Mineral Non Logam dan Batuan dengan Metode Monte Carlo - Santony, Julius (SEULANGA SYSTEM PUBLISHER, 2019)
Regional government in Indonesia annually sets a target for tax revenues of non-metallic minerals and rocks. Setting targets is very important as a guideline in preparing the current year's budget work plan. So far, the target of non-metal mineral and rock tax revenues has been prepared based on a joint agreement between the regional government and the regional legislature. The prediction of non-metal mineral and rock tax revenues using Monte Carlo simulation can be a solution to predict the next few years. This prediction uses data between 2009 - 2018 taken from the tax and retribution management body one of the districts in Indonesia. Testing the results of predictions is done by comparing the results of predictions with data from 2016 - 2018. The test results show that the average accuracy rate reaches 82.05%. So this study greatly helped the district government in setting the target for the acceptance of non-metal minerals and rock taxes.